The Application of the Strict Liability Principle in The Indemnity Laws for Livelihoods in Indonesia; Analysis of The Supreme Court’s Decision Number 1794K/PDT/G/2004 - Ahmad Tholabi Kharlie (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThis study is applied a descriptive-normative method which used to explain, describe, and analyze a particular event that is a proceeding submitted by the plaintiff against environmental pollution and damage, namely landslides on Mount Mandalawangi, using the concept of illegal acts The results of this study are: First, the compensation applied in the case of the Mount Mandalawangi landslide is based on the strict liability principle. The implication of the theory stated that the injured complainant is not required to prove the mistakes made by the defendant. Even if the defendant can prove that he is blameless, but there is a clear and proven impact of the loss in court, the defendant still obliged to pay for the compensation. Secondly, the Supreme Court's cassation decision is under the provisions of the prevailing laws and regulations in Indonesia, especially in the case of illegal acts, both confirmed in Article 1365 of the Civil Code (KUHPer) or regulated in the Protection Law and Environmental Management (UU-PPLH).Keywords: Environmental law, strict liability, claim for compensation, Supreme Court Abstrak:Studi ini bersifat deskriptif-normatif. Studi ini akan menjelaskan, menggambarkan, dan menganalisis suatu peristiwa tertentu yaitu suatu peristiwa tuntutan hukum yang diajukan oleh pihak penggugat yang terhadap pencemaran dan rusaknya lingkungan yaitu longsornya lahan di gunung Mandalawangi, dengan menggunakan konsep hukum perbuatan melanggar hukum. Adapun temuan dari studi ini adalah: Pertama, ganti kerugian yang diterapkan dalam kasus longsornya gunung Mandalawangi ini berdasarkan pada asas strict liability. Implikasi dari penggunaan teori tersebut, penggugat yang dirugikan tidak diharuskan untuk membuktikan kesalahan yang dilakukan oleh tergugat. Bahkan, bilapun tergugat dapat membuktikan bahwa dia tidak bersalah, namun ada dampak kerugian yang jelas dan dibuktikan di pengadilan, tergugat tetap memiliki kewajiban untuk membayar ganti kerugian tersebut. Kedua, putusan kasasi Mahkamah Agung sesuai dengan ketentuan peraturan perundang-undangan yang berlaku di Indonesia, terutama dalam hal perbuatan melawan hukum, baik yang ditegaskan dalam Pasal 1365 Kitab Undang-Undang Hukum Perdata (KUHPer) ataupun yang diatur di dalam Undang-Undang Perlindungan dan Pengelolaan Lingkungan Hidup (UU-PPLH).Kata kunci: Hukum lingkungan, strict liability, gugatan ganti rugi, Mahkamah Agung Аннотация В данном исследовании применяется описательно-нормативный метод, который используется для объяснения, описания и анализа конкретного события, представляющего собой судебную тяжбу, представленную истцом в отношении загрязнения и нанесению ущерба окружающей среды, а именно дело о лавине на горе Мандалаванги, с использованием концепции закона неправомерного акта. Полученные результаты в этом исследовании: Во-первых, компенсация, применяемая в случае схода лавины на горе Мандалаванги, основана на принципе Strict Liability. Вовлечение теории гласилo, что потерпевший истец не обязан доказывать ошибки, допущенные ответчиком. Даже если ответчик может доказать, что он невиновен, но существует явное и доказанное влияние потери в суде, ответчик все же обязан выплатить компенсацию. Во-вторых, кассационное решение Верховного суда соответствует положениям действующего законодательства и нормативных актов Индонезии, особенно в случае неправомерного акта, которые подтверждены в статье 1365 кодекса Гражданского права (KUHPer) или регулируются Законом о Защите и Регулировании Окружающей Среды (UU-PPLH).Ключевые слова: экологическое право, Strict liability, Тяжба о компенсации, Верховный суд